Foreign Direct Investment’s Impact on Nepal’s Economic Progress - Subedi, Raj Kumar (GS Spark: Journal of Applied Academic Discourse, 2024)
Foreign direct investment (FDI) plays a crucial role in the economic growth of developing countries like Nepal by bringing in essential capital, technology, and expertise. Over the past decade, Nepal has seen varying levels of FDI inflows, affecting different economic sectors. Despite its potential to attract more FDI, Nepal faces significant challenges, such as lengthy approval processes, implementation issues, and a bias towards the service sector among investors. Understanding the relationship between FDI and GDP, as well as the distribution of FDI across various sectors, is vital for optimizing investment policies and strategies. This study examines the factors influencing FDI and its sectoral distribution in Nepal’s economy from 2011/12 to 2020/21. It explores the relationship and effects of FDI on sectors like minerals, manufacturing, construction, energy, and services. Using a descriptive and correlational research design, the study analyzes annual time series data over a ten-year period. Statistical tools were employed to assess the correlation between FDI and GDP, as well as the impact of sectoral FDI investments on the country’s GDP. The study found a strong positive correlation (0.668) between FDI and GDP. Sectoral analysis revealed that investments in minerals, construction, energy, manufacturing, and services positively impact Nepal’s GDP. However, challenges like long approval processes, implementation issues, and investor bias towards the service sector hinder the full potential of FDI in higher-productivity sectors.